ANALISIS SIFAT TEKNIS TANAH PADA SISI LERENG UNDERPASS DI DESA KEBOCORAN KECAMATAN KEDUNGBANTENG KABUPATEN BANYUMAS (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2023)
In order to improve the welfare of the community in Banyumas Regency, the implementation of the Development Program in all fields, including transportation, buildings and so on, is carried out on an ongoing basis. One of the things that can be seen from the development to facilitate the transportation sector is the construction of an underpass in Kebocoran Village, with the aim of facilitating the transportation of road users in this area. However, there are several issues that are important to think about in the context of road construction, namely aspects of people's lives in several places, especially those related to the comfort and safety of road users. The existence of a slide on one side of the slope causes disruption of transportation routes around the underpass. ‘With the existence of these sliding conditions, it is necessary to review the technical and mechanical properties of the soil in that location, especially the certainty of the type of soil classification , the value of the water content, the value of the consistency limits for the value of soil density, as well as the value of the parameter of soil shear strength. Given these conditions, the Wijayakusuma University Purwokerto Faculty of Engineering Team through its Tri Dharma as a government partner feels responsible to participate in contributing or contributing knowledge to society. In this case, it is conveying the results of research that has been carried out on soil samples at that location’.